PENGENALAN DAN PEMAHAMAN KETERAMPILAN COMPUTATIONAL THINKING PADA TINGKAT SEKOLAH DASAR DESA SUKAMUKTI - Zaman, Muhammad Badru; Saparudin, Abdul Rohman; Rhamadan, M Firman; Rosmayanti, Destri; Al-ghifari, Abdullah; Syamsyul Arief, Zaenal; Rismawati, Rina; Ahsan, Muhammad Aulia; Alfarizi, Mohd Rayhan; Tsabitha Shahwa, Bella; Alfarizy, Muhamad Rezky; Rizky Linggardi, Gia; Ihsan Pratama, Nizar; Nur Rahayu, Sri; Rustandi, Agus; Febriyani; Fauzi, Muhammad Rifky; Aliansyah, Firman; Devalloh, Rifa; Al Waarits, Septa Hafizh (Jurnal PkM MIFTEK, 2025)
The lack of understanding of elementary school students in Sukamukti Village towards computational thinking skills is a major problem. To overcome this, a teaching program was introduced using the Bebras method which aims to introduce and improve students' understanding of thinking skills through a series of logical questions and challenges. This program was implemented in four elementary schools targeting grades 5 and 6. The results of the post-test showed that the average student understanding was still at an inadequate level, with an average score of 52.23. This indicates that although this program was successful in introducing the concept of CT, a more varied approach and longer teaching time are still needed to improve students' understanding.